The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/1521-3935(200207)203:10/11<1614::aid-macp1614>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactive blending of polyamide 6,6 and vectra A, 2

Abstract: In a previous paper Nylon 6,6/Vectra A blends have been prepared and investigated; in particular, our attention has been focused on Nylon 6,6 modifications due to interchange reactions that occur in the melt, as a function of mixing conditions and blend compositions, and improve the compatibility of the blend. The results indicated that only a small amount of copolymeric species form because of the low reaction kinetics and unfavorable physical and rheological aspects. In order to overcome these limits, a furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…In fact, the evaluation of morphometric parameters can provide quantitative and direct information on the filler dispersion and on the structure of the aggregates. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Furthermore, as the tensile and viscoelastic behaviour of composite materials is related to filler-filler and fillerelastomer interactions, mechanical and dynamicmechanical properties are generally used to study the rubber reinforcement. [1,[3][4][5]7,[10][11][12][18][19][20][21][22]25,[36][37][38][43][44][45][46][47][48][49][50][51][52][53]…”
Section: Full Papermentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the evaluation of morphometric parameters can provide quantitative and direct information on the filler dispersion and on the structure of the aggregates. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Furthermore, as the tensile and viscoelastic behaviour of composite materials is related to filler-filler and fillerelastomer interactions, mechanical and dynamicmechanical properties are generally used to study the rubber reinforcement. [1,[3][4][5]7,[10][11][12][18][19][20][21][22]25,[36][37][38][43][44][45][46][47][48][49][50][51][52][53]…”
Section: Full Papermentioning
confidence: 99%
“…[17,[39][40][41][42][43] To deepen the knowledge and attain a quantitative evaluation of the effect of surface modification on silica dispersion and rubber reinforcement, in the present contribution we report the results of a morphometric characterisation and of the dynamic-mechanical properties of compounds based on a styrene-butadiene random copolymer (SBR) loaded with different amounts of silica, either untreated or treated with TESPT and/or octadecyltriethoxysilane (ODTES). To this purpose, automated image analysis was performed on digitalised TEM micrographs and several morphometric descriptors -area (A), perimeter (P) and A/P ratio -were evaluated.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…In the core section of hybrid nanocomposite H1, the VA phase exists as droptlets, but not in smooth spherical shape as commonly seen in immiscible polymer blends. Most probably, such unique morphology was caused by the possible interchange reaction between nylon and VA [34]. For the core layer in H2 system, the VA phase still shows the fibril characteristic ( Fig.…”
Section: Materials Microstructurementioning
confidence: 99%
“…Moreover, previous works demonstrated that morphology and mechanical properties of in situ composites are affected by poor adhesion between the matrix and the TLCP [17,23]. Therefore, several routes were followed to improve compatibility, by modifying the TLCP fibre geometry, by chemical grafting of flexible polymer onto the TLCP fibre surface, by interchain reactions between the liquid-crystalline and the thermoplastic components, and by adding a second liquid-crystalline polymer partially miscible with both the reinforcing TLCP and the matrix [14,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%